Neutropenic enterocolitis associated with Clostridium tertium. Issue 2 (February 1993) - Coleman, N; Speirs, G; Khan, J; Broadbent, V; Wight, D G; Warren, R E
Abstract : A 15 year old boy being treated for relapsed acute lymphoblastic leukaemia developed severe diarrhoea and abdominal pain which worsened despite empirical antibiotic treatment. A right hemicolectomy was performed. The caecum and ascending colon showed changes typical of neutropenic enterocolitis. Clostridium tertium was isolated from faeces, blood cultures, and from the resected gut wall, with no evidence of other organisms capable of causing such a condition. As far as is known, this is the first reported case in which neutropenic enterocolitis has been associated with well documented C tertium infection, an organism previously described as a cause of bacteraemia in neutropenic patients.